Theoretical model of trust-based relationships in building information modelling supply chain for construction projects - Olugboyega, Oluseye; Windapo, Abimbola (Acta Structilia, 2019)
The structure of relationships among project participants has a significant impact on trust development, while the number of participants involved in the relationship increases the complexity of trust. Hence, it becomes inappropriate to generalise the existing dimension and components of trustbased relationships to trust-based relationships among the building information modelling (BIM) supply chain members because of the multiple structures of relationship and the numerous interpersonal and inter-organisations that participate on BIM-based construction projects. This article investigates the nature of trust-based relationships among the BIM supply chain members and establishes whether the requirements of the BIM process influence trust-based relationships among the BIM supply chain members. A five-stage PRISMA was adopted for systematic reviews and meta analysis. The systematic review enabled the development of a theoretical model of trustbased relationships in BIM supply chain which was subjected to meta-analysis for validation. The findings revealed that trust-based relationships among the BIM supply chain members entail trusting and trustworthy behaviours, positive expectations, and positive reputations, under which twenty-seven components were identified and classified appropriately. The article concludes that the nature of trustbased relationships among the BIM supply chain members, as influenced by the requirements of the BIM process, can be explained as trusting and trustworthy behaviours, positive expectations, and positive reputations. The article advances the understanding of trust-based relationships among the BIM supply chain members and recommends a first-hand investigation into the nature of trust-based relationships among the BIM supply chain members in future studies.